Perkebunan Teh Medini Sebagai Agrowisata Kabupaten Kendal - Ferosa, Delilah Zsalzsa; Luthfia, Daimatul Ilma; Septian, Asya Ainu; Kiflaini, Tazkiyyah Hanik; Ainunnisa, Hanifah (Jurnal Ekonomi Pertanian dan Agribisnis, 2025)
This research aims to analyze the development potential of Medini Tea Garden as an agro- tourism destination in Kendal Regency, as well as identify challenges and relevant development strategies. This research uses qualitative approach with literature study as data collection method. The results showed that Medini Tea Garden has great potential as an agritourism destination, supported by natural beauty, educational potential, and high cultural value. However, there are several challenges that need to be overcome, such as waste management, environmental conservation, and community involvement. To develop agritourism sustainably, it is recommended to diversify tea-based products, improve tourist facilities, implementsustainable agricultural practices, and involve the community in management. This study concludes that with proper management, Medini Tea Garden can be a model of sustainable agritourism development and provide economic and social benefits for the surrounding community.